Stability assessment of a road cut slope using 3d numerical simulation – a case study - Sardana S.; Sinha R.K.; Jaswal M.; Verma A.K.; Singh T.N. (My University, 2025)
Three-dimensional numerical simulation has been used to examine the stability of a road cut slope in the Himalayan region of India. The site investigation has been carried out to collect data and rock samples. The geometry of the slope has been prepared in the numerical software to represent the actual slope and the major joints sets were mapped in the numerical model as per their dip/dip-direction observed at the site. The behaviour of the discontinuity sets was modelled using a Mohr-Coulomb slip with residual strength. The normal stiffness of the joints was calculated from rock mass deformation modulus, intact rock young’s modulus and joint spacing. Similarly, the shear stiffness has been calculated. The results show the total displacement of 10.6 cm with a total velocity of 0.43 m/s for the same block in the numerical analysis. © 2020 ISRM.